Finland’s Antarctic Research Strategy - Coordination Committee for Antarctic Research. Chair Petteri Kauppinen and secretary Riina Vuorento (opetus- ja kulttuuriministeriö, 2014)
On 2 March 2012 the Ministry of Education and Culture appointed a Coordination Committee for Antarctic Research for the period 2012-2014. The task of the Committee was to update the national Antarctic research strategy, strengthen national Arctic research co-operation, promote Finland’s involvement in international Antarctic research co-operation, promote awareness and discussion on Antarctic research and monitor Finland’s Antarctic research results and adherence to international obligations. The Coordination Committee for Antarctic Research endorsed Finland’s Antarctic Research Strategy 2014 at its meeting on 28 March 2014. The Committee consulted the science community and other Antarctic research stakeholders in the preparation of the strategy. Antarctic research will produce high quality scientific data that concern Antarctica or for which information obtained from Antarctica is irreplaceable. Research may be either global, or limited to the two Polar Regions, but it would not be possible without data from Antarctica. Moreover, the research will generate information to support national and international decision-making. In Finnish Antarctic research the emphasis is especially on the areas of strength where Finland can conduct high-quality international scientific research. Antarctic research strengthens expertise on cold-climate conditions in Finland. The Coordination Committee for Antarctic Research defined its vision for Finland’s Antarctic research, according to which: - Finnish Antarctic research is of high international standard and open to new directions. The vision of Finland’s Antarctic research strategy is carried out through three focus areas: 1. Based on unique data, Antarctic research produces new scientific breakthroughs. 2. Antarctic research is internationally interactive. 3. Adequate prerequisites for Antarctic research are ensured and consistently developed.